Hubungan Tabungan Nasional, Akumulasi Modal, dan Pertumbuhan Output di Indonesia 2020–2024: Analisis Teoretis dan Empiris Berdasarkan Model Solow–Swan - Febri Delmi Yetti; Ayus Ahmad Yusuf (IAIN Langsa, 2026)
This study examines the relationship between national savings, capital accumulation, and economic growth in Indonesia during the period 2020–2024 by integrating conventional growth theory (Solow–Swan and Blanchard) with Islamic economic perspectives, including maqasid al-shariah, risk-sharing mechanisms, and Islamic financial instruments. Using secondary data from BPS, Bank Indonesia, OJK, and the Ministry of Finance, this research applies descriptive–quantitative analysis, Pearson correlation, and steady-state simulations to evaluate Indonesia’s growth dynamics. The findings show that Indonesia’s national saving rate (33–34% of GDP) reflects strong domestic financial capacity but remains below the estimated golden rule level. Investment efficiency is also relatively low, as indicated by a high ICOR (6–7), suggesting limited output gains from capital accumulation. The positive correlation between savings and output (r ≈ 0.78) mainly reflects macroeconomic stability rather than long-term causality. Furthermore, Islamic financial instruments such as sovereign sukuk, profit-sharing financing, productive waqf, and ZISWAF demonstrate significant potential to improve capital efficiency and promote inclusive and sustainable economic growth.